The COVID-19 Pandemic in the Social Teaching of the Roman Catholic Church - H. T. Sardaryan (Vestnik MGIMO-Universiteta)
The COVID-19 pandemic exposed the critical problems of the structure not only of the modern health system but also of the role of the state in managing socio-economic processes, government institutions, and their ability to ensure the safety and well-being of the population in conditions of the practical economic shutdown, self-isolation of citizens and ultra-high mobilization of state administrative resources to ensure a full-scale fight against the spread of the virus. Inherent human rights and freedoms were limited to effectively counter the coronavirus, which would have been difficult to imagine even a few months before the pandemic outbreak. Arguments about the gradual decline of the role of the state in the organization of the management of socio-economic processes against the background of the strengthening of civil society institutions also lost their significance, as only the state was able to organize a centralized mobilization of resources to counter the mass threat to public health. These questions lead to a revision of the traditional axiology of Western society, based on the primacy of individualism and the atomization of society – approaches that the Roman Catholic Church has traditionally opposed, which in its doctrine is based on the concept of the common good. As the world's largest confession, Catholicism retains its influence over a wide range of people in many of the leading countries of the modern West. The church's social doctrine is traditionally perceived, both by Catholics themselves and by various associations of citizens, as an ethical basis for organizing the life of society. The paper analyzes the development of the social doctrine of the Catholic Church after the outbreak of the pandemic in the context of both its perception of the coronavirus itself and the necessary measures to combat it and its position on the post-ovoid structure of the world. The Papal encyclicals, messages, and speeches, which reflect the official position of the Vatican, are of crucial importance. As a possible way to overcome the crisis, the Vatican offers the classic principles for the social teaching of the Catholic Church-solidarity and subsidiarity, which require, on the one hand, the subjectivity of society and the decentralization of power.